A systematic review and meta‐synthesis of qualitative studies that investigate the emotional experiences of staff working in homeless settings. (13th July 2021) - Peters, Louise; Hobson, Christopher W.; Samuel, Victoria
Abstract: Homelessness is a pervasive issue in society, and government policies have highlighted the need to focus on the experience of front‐line staff in homelessness settings. The aim of this meta‐synthesis was to draw together the available research to further understanding of the experiences of staff working with homeless people. A systematic search was conducted across four electronic databases (ASSIA, PsycInfo, Sociological Abstracts and Web of Science) from the date of their inception. Qualitative research exploring the emotional experiences of staff working in homeless settings was identified. Identified studies were subject to quality assessment, and the data were synthesised using meta‐ethnography. Ten studies were included in the synthesis following screening of 228 titles, 92 abstracts and 33 full texts. The concepts that were obtained from the analysis were building quality relationships, negotiating boundaries, carrying the emotional burden (self and others), accessing care and support (self‐care and from others), individual advancement, advocating and contextual helplessness. An overarching theoretical construction of the internal experiences of support staff in managing the demands of the role along with their own needs was developed. This theory may provide the basis for testable hypotheses in future research and inform the development of support and training opportunities for staff working within homelessness settings.